Evaluasi Kinerja Lulusan Program Studi Pendidikan Teknik Mesin Universitas Sebelas Maret Di Dunia Kerja - Agus Hardika; Yuyun Estriyanto; Indah Widiastuti (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
Evaluation of the performance of study program graduates in the world of work is one indicator of higher education quality. The high performance of graduates and their relevance to the needs of the world of work indicate a good quality higher education. The purpose of this study is to evaluate the performance of graduates of Sebelas Maret University Mechanical Engineering Education (PTM UNS) in the world of work. So that the results obtained as a priority reference for learning development in study programs and students. This research is quantitative descriptive. It is carried out through a tracer study of graduate data and a survey of graduate users. The subjects of this research include UNS PTM graduates who graduated in 2016, 2017 and 2018 as a source of tracking data for graduates and 80 graduate users as a source of satisfaction survey data and the level of importance of the formulated Graduate Learning Outcomes (CPL). Data collection techniques were carried out through the method of filling out the questionnaire instrument questionnaire. The analysis was carried out using quantitative descriptive statistical analysis techniques using the SPSS V.21 data processing application. The results of this study show profile data for PTM UNS graduates, namely the average graduate with a very satisfactory predicate (GPA 3.46) with an average study period of 4 years and 2 months. Most (56%) work as educators, with a high level of suitability of work with the field of science 47.5%; 38.9% moderate and the remaining 13.6% low. The average waiting time for the first job after graduation is less than 6 months (76.5%). Furthermore, for the results of the graduate user satisfaction survey, the average total satisfaction is 4.28 (very satisfactory). With an importance level of 12 Graduate Learning Outcomes (CPL), 11 of them are in the very important category and one is in the important category (T8). Objectively, users are satisfied with the performance of graduates, but subjectively researchers need to propose development priorities for study programs based on the value of the level of satisfaction which is below the total average value. The conclusion in this study shows that the performance of graduates of the PTM UNS study program has been good or satisfactory. However, there is a need for a program to improve the quality of graduate performance in the communication and professional aspects. It is hoped that the study program will be able to improve the quality of these two aspects through improving the quality of learning, infrastructure and learning facilities as well as improving the quality of educators/lecturers.